Katolikkernes stilling og antikatolicismen i Danmark 1800-1849 - Møller, Jes Fabricius (Kirkehistoriske Samlinger, 2012)
Summary Catholics and anti-Catholicism in Denmark 1800-1849 The status of Catholics in the Oldenburg conglomerate state was based on the written absolutist constitution, Lex Regia, from 1665 according to which the the King “must honor, serve and worship the one true God according to the way that He in his holy and true word has revealed to us and according to what our Christian Faith informs us in the shape and form given by the Augsburg Confession 1530”. Catholic mission was theoretically a capital offence but in reality Catholics were tolerated to a certain degree. The King permitted Catholics to build churches in a few towns. In the colonies religious freedom was greater than in Denmark proper. There were only very few non-Protestants in Denmark. After 1800 Catholics were still discriminated against and harassed but there was a general tendency towards more religious freedom and tolerance against religious minorities in general and a tendency to have a more amicable view of Catholics in particular connected to the romanticist’s positive attitude towards anything medieval. Official animosity against Catholic activities in the Danish realm was often politically motivated. The Pope was seen as a foreign potentate challenging the sovereignty of the Danish Monarch rather than the purity of the faith. In the Constitutional Assembly 1848-49 freedom of religion was one of the most debated issues. Distrust and dislike of Catholics in general and Jesuits in particular was often and vociferously displayed but the principle of freedom of religion won the majority of votes. In the following generations the Catholic Church in Denmark grew under the protection of the law and in an environment of increasing acceptance and tolerance.